Analisis Sifat Mekanik dan Permukaan pada Degradasi Plastik Konvensional - Ristika Oktavia Asriza; Nurhadini Nurhadini; Qothrunnada Nur Azizah; Amelia Narulita (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Currently, plastic waste that decomposes for a long time can damage the environment and natural ecosystems. therefore, an innovation was made to create an environmentally friendly plastic that decomposes faster in nature. The purpose of this research is to determine the degradation ability of environmentally friendly conventional biodegradable plastics. This research uses environmentally friendly conventional plastic materials. This plastic is degraded in 3 (three) ways, namely photodegradation (irradiation with UV C light), irradiation with sunlight, and biodegradation. Each degradation process lasts for 30 days. The research results showed that there was a decrease in the elongation at break value of plastic that had been degraded. This is caused by the breaking of bonds in the polymer chain. Apart from that, the plastic also experiences damage to its surface. This damage is characterized by cracks, the appearance of stains, and the appearance of mold or microorganisms on the plastic surface.